you first multiply the second system all by 2, and you get
10x+6y=-18
then, you had the 2 equations together, thus eliminating the y's
you get: 11x=33 so x=3. then plug in x into either of the equations to find y
2006-12-07 16:30:43
·
answer #1
·
answered by bree 3
·
0⤊
0⤋
Lemme guess. Homework?
x - 6y = 51----------------(eqn1)
5x + 3y = -9 --------------(eqn2)
Multiply eqn2 by 2.
>>> x - 6y = 51
>>> 10x + 6y = -18.
Now add the equations, 6y and -6y get canceled and you're left with
11x = 33
x= 33/11 = 3
Now substitute x = 3 and solve for y.
GoodLuck!
2006-12-07 16:29:18
·
answer #2
·
answered by Yvonne Mystic 4
·
0⤊
0⤋
x - 6y = 51
5x + 3y = -9
Your first step is to multiply the first equation by -5. Then you get
-5x + 30y = -255
5x + 3y = -9
Now, add the two equations together. This should eliminate the x variable.
(-5x + 30y) + (5x + 3y) = -255 - 9
33y = -264
y = -8
Plug in y = -8 into one of the other two equations and solve for x.
2006-12-07 16:32:32
·
answer #3
·
answered by Puggy 7
·
0⤊
0⤋
multiply the second system by 2 on both sides to give you
10x+6y=-18 and now add it to the first system
x-6y=51
and the y's cancel giving you
11x=33
so x=3
now substitute into either of the equations to give you y
(3)-6y=51
-6y=48
y=-8
2006-12-07 16:30:27
·
answer #4
·
answered by White Lightning 2
·
0⤊
0⤋
1.
(5)x - 6y = 51(5)
(-1)5x + 3y = -9(-1)
2.
5x - 30y = 255
-5x - 3y = 9
-33y = 264
y= -8
2006-12-07 16:38:33
·
answer #5
·
answered by pepsi 2
·
0⤊
0⤋
(1) X - 6Y = 51
(2) 5X + 3Y = -9
1* (1) X - 6Y = 51
2 * (2) 10X + 6Y = -18
------------------------------ +
11X = 33
X = 3
(2) 5X + 3Y = -9
5(3) + 3Y = -9
3Y = -9 - 15
3Y = -24
Y = -8
2006-12-07 16:32:38
·
answer #6
·
answered by Imoet 2
·
0⤊
0⤋